Reversible al metal anodes enabled by amorphization for aqueous aluminum batteries - Yan, Chunshuang (2022)
Aqueous aluminum metal batteries (AMBs) are regarded as one of the most sustainable energy storage systems among post-lithium-ion candidates, which is attributable to their highest theoretical volumetric capacity, inherent safe operation, and low cost. Yet, the development of aqueous AMBs is plagued by the incapable aluminum plating in an aqueous solution and severe parasitic reactions, which results in the limited discharge voltage, thus making the development of aqueous AMBs unsuccessful so far. Here, we demonstrate that amorphization is an effective strategy to tackle these critical issues of a metallic Al anode by shifting the reduction potential for Al deposition. The amorphous aluminum (a-Al) interfacial layer is triggered by an in situ lithium-ion alloying/dealloying process on a metallic Al substrate with low strength. Unveiled by experimental and theoretical investigations, the amorphous structure greatly lowers the Al nucleation energy barrier, which forces the Al deposition competitive to the electron-stealing hydrogen evolution reaction (HER). Simultaneously, the inhibited HER mitigates the passivation, promoting interfacial ion transfer kinetics and enabling steady aluminum plating/stripping for 800 h in the symmetric cell. The resultant multiple full cells using Al@a-Al anodes deliver approximately a 0.6 V increase in the discharge voltage plateau compared to that of bare Al-based cells, which far outperform all reported aqueous AMBs. In both symmetric cells and full cells, the excellent electrochemical performances are achieved in a noncorrosive, low-cost, and fluorine-free Al2(SO4)3 electrolyte, which is ecofriendly and can be easily adapted for sustainable large-scale applications. This work brings an intriguing picture of the design of metallic anodes for reversible and high-voltage AMBs.